ANALISIS TERJEMAHAN IF CLAUSA (KLAUSA IF) STUDI KASUS TERJEMAHAN NOVEL THE LOST SYMBOL DARI BAHASA INGGRIS KE DALAM BAHASA INDONESIA - Yulia Fitra (Balai Bahasa Sumatera Utara, 2019)
This research is about An Analysis of If Clause, A Case Study in Dan Browns The Lost Symbol and Its translation into Bahasa Indonesia by Inggrit Dwijani Nimpoeno. The purpose of this study was to identify some methods that is used by translator to translate if clause from English into Bahasa Indonesia and to describe translation techniques used by translator. The research method used in this research is qualitative descriptive. Applying Newmark translation method to identify the data which is drawn in a diagram called V diagram. In this translation, there are two emphasizes those are source and target languages. The research result shows that among 240 if clause found data present that translator use several methods such as word for word translation for 134 (55,84%) if clause data, free translation for 83 (34,58%) data, and literal translation for 23 (9,58%) data. The most used translation oriented to source language that is word for word translation.